Thermal stress in bimetallic receiver of solar parabolic trough concentrator induced due to non uniform temperature and solar flux distribution. (December 2018) - Khanna, Sourav; Sharma, Vashi; Newar, Sanjeev; Mallick, Tapas K.; Panigrahi, Pradipta Kumar
Highlights: Mathematical equations are derived to calculate stress in double-layered absorber. Change in HTF flow rate 0.4–1.4 kg/s reduces stress from −127 MPa to −86 MPa. Use of high conductivity material as outside layer reduces stress to −38 MPa. Focal-length of 0.7 m reduces stress to negligible value for 3rd generation Luz PTC. Abstract: The absorber-tube of the parabolic trough collector (PTC) witnesses compression and tension while operation due to the thermal gradient developed over the cross-section of the tube. While the researchers have proposed a number of receiver models to improve the energy collection by heat transfer fluid inside the absorber-tube, the stress developed that forms the essential frameworks for the tube's and glass-envelope's safety has not been modelled for real life scenarios where the absorber is held at a number of pillars. The current study models the stress due to compression and tension in a double-layered absorber (held at pillars) having a high conducting material's layer to mitigate the risk of stress significantly. The pillars are movable that ensure the smooth elongation of the absorber-tube under stress. The pillars are equipped with ball-joints that help the tube to rotate in longitudinal plane. The verification of the proposed model has been carried out against the reported results. The impact of placing the high conductive material as inside or outside layer of the double-layered absorber, width and focal-length of PTC, HTF's rate of flow, and the geometrical imperfections on the normal-stress are found out. The performance of the modelled double-layered absorber is observed in contrast with the single-layered one. It is concluded that (i) the single-layered absorber witnesses stress of −127 MPa/+101 MPa due to compression/tension. The one with double-layer undergoes lesser respective stress of −78 MPa/+59 MPa when the high conductivity material is placed on the inner side. Besides, the use of high conductivity material as outside layer reduces the stress further to −38 MPa/+35 MPa. Thus, for minimum stress, the outside layer should always be made up of high conducting material, (ii) increasing the HTF's rate of flow from 0.4 kg/s to 1.4 kg/s results in the reduction of stress from −127 MPa/+101 MPa to −86 MPa/+66 MPa for single-layered absorber. For double-layered absorber, stress comes down from −38 MPa/+35 MPa to −29 MPa/+26 MPa and (iii) an appropriate focal-length of around 0.7 m results in the reduction of stress to almost negligible value of 3 MPa for 3rd generation Luz PTC.